2004
DOI: 10.1158/0008-5472.can-03-0160
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Matrix Metalloproteinase-9 Regulates the Vascular Architecture in Neuroblastoma by Promoting Pericyte Recruitment

Abstract: 004). MMP-2 is expressed by neuroblastoma tumor cells and stromal cells, whereas MMP-9 is exclusively expressed by stromal cells, particularly vascular cells.To examine the contribution of MMP-9 to tumor angiogenesis, we generated RAG1/MMP-9 double-deficient mice. We observed a significant inhibition of angiogenesis in the immunodeficient RAG1/MMP-9 double-deficient mice orthotopically implanted with tumor cells (P ‫؍‬ 0.043) or implanted s.c. with a mixture of tumor cells and Matrigel (P < 0.001). Using an FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
174
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(187 citation statements)
references
References 46 publications
11
174
1
1
Order By: Relevance
“…Our results are in accordance with those of previous reports showing that a high MMP-9 expression correlates significantly with tumoral aggressiveness and poor prognosis (Chantrain et al, 2004;Li et al, 2004;Pellikainen et al, 2004), as well as with other studies where high MMP-2 expression in carcinoma cells, in contrast, has been related to only a few inverse prognostic factors (Talvensaari-Mattila et al, 1998;Nakopoulou et al, 2003) or shown to have no association with clinicopathological parameters in breast cancer (Jones et al, 1999;Hirvonen et al, 2003;Talvensaari-Mattila et al, 2003). It has also been described that as breast cancer progresses, MMP-2 production increases during the early phases, whereas activation of MMP-9 occurs during the late cancerous stage (Liotta and Kohn, 2001), which could explain their different impact on prognosis in clinically detected invasive breast tumours.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accordance with those of previous reports showing that a high MMP-9 expression correlates significantly with tumoral aggressiveness and poor prognosis (Chantrain et al, 2004;Li et al, 2004;Pellikainen et al, 2004), as well as with other studies where high MMP-2 expression in carcinoma cells, in contrast, has been related to only a few inverse prognostic factors (Talvensaari-Mattila et al, 1998;Nakopoulou et al, 2003) or shown to have no association with clinicopathological parameters in breast cancer (Jones et al, 1999;Hirvonen et al, 2003;Talvensaari-Mattila et al, 2003). It has also been described that as breast cancer progresses, MMP-2 production increases during the early phases, whereas activation of MMP-9 occurs during the late cancerous stage (Liotta and Kohn, 2001), which could explain their different impact on prognosis in clinically detected invasive breast tumours.…”
Section: Discussionsupporting
confidence: 93%
“…Similar conclusions for MDA-MB-231 cells have been recently suggested (Suarez-Cuervo et al, 2004). In addition to above-mentioned mechanisms, recent studies have suggested that MMP-9 may promote tumor angiogenesis by recruiting pericytes along vascular endothelial cells (Chantrain et al, 2004), via a release of soluble c-kit ligand (Heissig et al, 2002), and by recruiting bone marrow-derived precursor cells to the tumor stroma (Jodele et al, 2005). Thus, multiple mechanisms may operate downstream of TGF-b-ALK5 signaling to enhance tumor angiogenesis and our results indicate that MMP-9 is a critical component of this program.…”
Section: Discussionsupporting
confidence: 81%
“…Although it is well documented that MMP-9 is required for tumor progression (Bergers et al, 2000;Welch et al, 2000), the source of MMP-9 is still a subject of discussion. It has been shown that MMP-9 is secreted by tumor cells (Farina et al, 1998;Janji et al, 1999;Suarez-Cuervo et al, 2004) as well as by cells residing in stromal compartments (Chantrain et al, 2004;Jodele et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…MMP9 and MMP14 have another effect on the vasculature: the perivascular (or smooth muscle) cells that ensheath the endothelial cells of the blood vessels are missing or their density is significantly decreased in normal vessels and during tumour neoangiogenesis [57][58][59] . This defect is especially evident in the smaller arterioles of the brain, and many of the remaining perivascular cells have irregular morphology.…”
Section: Mmps In Blood-vessel Remodellingmentioning
confidence: 99%